49.9k views
4 votes
I need to know these asap

I need to know these asap-example-1

1 Answer

1 vote

Answer: (-3, -5)

Explanation:

-6x + y = 13

6x + 3y = -33

4y = -20

÷4 ÷4

y = -5

6x + 3y = -33

6x + 3(-5) = -33

6x - 15 = -33

6x = -18

x = -3

*********************************************************************************

Answer: (
(1)/(3), 2)

Explanation:

9x + y = 5 → 1(9x + y = 5) → 9x + y = 5

3x - 3y = -5 → -3(3x - 3y = -5) → -9x + 9y = 15

10y = 20

÷10 ÷10

y = 2

9x + y = 5

9x + (2) = 5

9x = 3

x =
(1)/(3)



User Vikiiii
by
6.0k points